Comparative Study: The Development of Islamic Economics and Finance Industry in the UK, The United States, and Indonesia - Toatubun, Maimunah; Holle, Mohammad Hanafi (Fakultas Hukum Universitas Djuanda, 2025)
The existence of Lariba financial institutions is the starting point for the development of Islamic Banking, Sukuk, and Takaful which are utilized by the community. Indonesia has experienced improvements in terms of Islamic banking, sukuk, and takaful. The obstacles faced are regulations that have not fully supported the implementation of Islamic values, understanding and lack of human resources. America is faced with the obstacle of the attitude of the community who still do not accept the existence of Islamic law. Lack of support from the US government and minimal infrastructure. Indonesia lacks human resources, low levels of literacy and financial inclusion make the development of Islamic economics and finance slow. However, the three countries have very large prospects and potential in the development of the Islamic economy and financial industry. The British government is serious about development by creating work programs, Islamic financial service regulations, changing tax treatment using the Islamic financial system, and providing funding assets and support for educational institutions. The US government provides freedom for the community to invest in Islamic financial institutions and also provides flexibility for the establishment of Islamic economic and financial education institutions. The Indonesian government has established a number of institutions tasked with developing Islamic economics and finance, through an Islamic banking roadmap, an Islamic banking blueprint, and the development of educational institutions that provide Islamic economics, business, and finance studies, both at Islamic and general universities.